PERANCANGAN SISTEM INFORMASI JASA SERVIS PADA ASTRA HONDA GANDARIA JAKARTA - Rian, Hesti (POLITEKNIK LP3I JAKARTA, 2014)
An information system in a company can improve performance and simplify work processes , especially in the case that requires speed and accuracy of data. This study can be used as input that can be developed with respect to the issues discussed to help the performance of Astra Honda Gandaria in running the company . Information system design service bike shop at Astra Honda Gandaria Jakarta using the method of observation , interviews, and literature . With the computerized system service bike shop at. Astra Honda Gandaria provide information about the activities that occur with detailed service making it easier for the owners or employees of PT . Astra Honda Gandaria obtain a clear and accurate information.Keyword : Innformation System Development